Organ-specific bacterial communities of the soft-shell clam Mya arenaria (Linnaeus, 1758) and adjacent sediments in the Black Sea - Menabit, Selma; Lavin, Paris; Begun, Tatiana; Teacă, Adrian; Mureşan, Mihaela; Purcarea, Cristina (Frontiers in Marine Science, 2025)
Bacteria colonizing bivalves play a critical role in host health by supporting digestion, nutrient cycling, and immune defense. While the microbiomes of marine bivalves have been studied globally, their diversity and functional roles across specific organs remain underexplored. This study investigates the structural and predicted functional diversity of bacterial communities associated with different organs (siphon, gills, and stomach) of the marine bivalve Mya arenaria Linnaeus, 1758, along with the surrounding sediments from the Romanian Black Sea coast, using 16S rRNA gene sequencing with Illumina technology. Bacterial communities within the bivalve differed markedly from those in the sediments and varied across organs. Sediment samples exhibited greater taxonomic diversity (19 phyla) than bivalve organs (14–15 phyla). Verrucomicrobiota dominated the siphon and gills, Spirochaetota were most abundant in the stomach, and Desulfobacterota predominated in sediments. Nitrate-reducing bacteria, particularly those from the genus Persicirhabdus, were prevalent in all organs and may contribute to host resilience under hypoxic conditions. The presence of Sulfurimonas in the stomach suggests a possible nutritional association, while halotolerant Woeseia species identified in sediments likely play a role in environmental nutrient cycling. Predictive functional profiling indicated potential bacterial involvement in various metabolic processes, including carbohydrate, amino acid, and energy metabolism. Additionally, pathways related to xenobiotic degradation and antibiotic biosynthesis were inferred across all sample types, indicating a potential capacity for broader ecological and possibly biotechnological roles. However, these functions were inferred from 16S rRNA data and require further validation through metagenomic or transcriptomic approaches. To our knowledge, this is the first detailed analysis of microbiome variability across different organs of M. arenaria, offering new insights into host–microbe interactions in this species.